Les loisirs nautiques dans l’estuaire de la Seine : Médiations territoriales, consciences du milieu - Damien Femenias; Olivier Sirost; Barbara Evrard (VertigO)
This article explores the socio-natural reality of the Seine river estuary that has been constructed by the practice of water sports. We were particularly interested in the mediations produced by these practices. How do territorial mediations and aesthetic constructions provide access to or serve as a screen for an awareness of the estuary environment? The article shows a fragmented estuary, very unevenly visited, and proposes a typology of the principal forms of sport. The ocean, the urban Seine and the Seine around the islands have three distinct relationships with the turbid waters of the river: what are they? The heterogeneity of usages and perceptions can be explained by the multiscalar management of the estuary space and by the horizons of expectation for the various sports practices. Understanding what the public does in nature thus provides insight into perceptions about the environment and suggests new questions about the management of ecosystems, whether this concerns measures of compensation, protection or recovery.